2018
DOI: 10.3897/zookeys.759.24129
|View full text |Cite
|
Sign up to set email alerts
|

A DNA barcode library for ground beetles of Germany: the genus Amara Bonelli, 1810 (Insecta, Coleoptera, Carabidae)

Abstract: The genus Amara Bonelli, 1810 is a very speciose and taxonomically difficult genus of the Carabidae. The identification of many of the species is accomplished with considerable difficulty, in particular for females and immature stages. In this study the effectiveness of DNA barcoding, the most popular method for molecular species identification, was examined to discriminate various species of this genus from Central Europe. DNA barcodes from 690 individuals and 47 species were analysed, including sequences fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 91 publications
1
15
0
Order By: Relevance
“…Unique BINs were revealed for 44 species (86%) of the analyzed 51 taxa. This result coincides with high rates of successful species identification of previous barcoding studies in terms of carabid beetles (Raupach et al 2010;Raupach et al 2011;Pentinsaari et al 2014;Hendrich et al 2015;Raupach et al 2018). Nevertheless, the data revealed some species pairs with low interspecific distances (< 2.2%) and shared haplotypes but also three species with intraspecific distances > 2.2%.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Unique BINs were revealed for 44 species (86%) of the analyzed 51 taxa. This result coincides with high rates of successful species identification of previous barcoding studies in terms of carabid beetles (Raupach et al 2010;Raupach et al 2011;Pentinsaari et al 2014;Hendrich et al 2015;Raupach et al 2018). Nevertheless, the data revealed some species pairs with low interspecific distances (< 2.2%) and shared haplotypes but also three species with intraspecific distances > 2.2%.…”
Section: Discussionsupporting
confidence: 90%
“…In recent years, various barcode libraries for numerous animal groups of Germany were established, including both marine and freshwater fish (Knebelsberger et al 2014;Knebelsberger et al 2015), amphibians and reptiles (Hawlitschek et al 2016), echinoderms (Laakmann et al 2017), molluscs (Gebhardt and Knebelsberger 2015;Barco et al 2016), crustaceans (Raupach et al 2015), spiders (Astrin et al 2016), myriapods (Spelda et al 2011), and numerous insect taxa, e.g., Coleoptera (Hendrich et al 2015), Ephemeroptera, Plecoptera, Trichoptera (Morinière et al 2017), Heteroptera (Raupach et al 2014;Havemann et al 2018), Hymenoptera (Schmidt et al 2015;Schmidt et al 2017;Schmid-Egger et al 2019), Lepidoptera (Hausmann et al 2011), Neuroptera (Morinière et al 2014), and Orthoptera (Hawlitschek et al 2017). Previous studies also laid the groundwork of a comprehensive DNA barcode library for the ground beetles (Coleoptera: Carabidae) of Germany (Raupach et al 2010;Raupach et al 2011;Hendrich et al 2015;Raupach et al 2016;Raupach et al 2018;Raupach et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This local sequence database consists of the compiled data which are based on the DNA library with more than 23,000 barcoded German animal species assembled in two major DNA barcoding campaigns: “Barcoding Fauna Bavarica” (BFB, http://www.faunabavarica.de, Haszprunar, 2009) and “German Barcode of Life” project (GBOL, http://www.bolgermany.de, Geiger et al, 2010), with nearly 250,000 vouchers curated at the Zoological State Collection Munich, Germany (http://www.barcoding-zsm.de). Data releases have been published for all major arthropod groups, that is, Coleoptera (Hendrich et al, 2015; Raupach, Hannig, Moriniere, & Hendrich, 2016; Raupach, Hannig, Morinière, & Hendrich, 2018; Rulik et al, 2017), Diptera (Morinière et al, 2019), Ephemeroptera, Plecoptera, and Trichoptera (Morinière et al, 2017), Heteroptera (Havemann et al, 2018; Raupach et al, 2014), Hymenoptera (Schmid‐Egger et al, 2019; Schmidt, Schmid‐Egger, Morinière, Haszprunar, & Hebert, 2015; Schmidt et al, 2017), Lepidoptera (Hausmann, Haszprunar, & Hebert, 2011a; Hausmann, Haszprunar, Segerer, et al, 2011), Neuroptera (Morinière et al, 2014), Orthoptera (Hawlitschek et al, 2018), Araneae and Opiliones (Astrin et al, 2016), and Myriapoda (Spelda, Reip, Oliveira Biener, & Melzer, 2011; Wesener et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Currently, the DNA barcode library created by the ZSM researchers represents the second‐most comprehensive library of any nation. Previous studies have reported on barcoding results for Coleoptera (Hendrich et al, ; Raupach, Hannig, Moriniere, & Hendrich, ; Raupach, Hannig, Morinière, & Hendrich, ; Rulik et al, ), Ephemeroptera, Plecoptera and Trichoptera (Morinière et al, ), Heteroptera (Havemann et al, ; Raupach et al, ), Hymenoptera (Schmid‐Egger et al, ; Schmidt, Schmid‐Egger, Morinière, Haszprunar, & Hebert, ; Schmidt et al, ), Lepidoptera (Hausmann, Haszprunar, & Hebert, ; Hausmann, Haszprunar, Segerer, et al, ), Neuroptera (Morinière et al, ), Orthoptera (Hawlitschek et al, ), Araneae and Opiliones (Astrin et al, ), and Myriapoda (Spelda, Reip, Oliveira Biener, & Melzer, ; Wesener et al, ). Concerning DNA barcoding studies performed for Diptera, no comprehensive study encompassing this entire highly diverse order has been published, but data have been used to revise smaller units thereof: for example, for Calliphoridae (Jordaens et al, ; Nelson, Wallman, & Dowton, ; Reibe, Schmitz, & Madea, ), Ceratopogonidae (Stur & Borkent, ), Chironomidae (Carew, Pettigrove, Cox, & Hoffmann, ; Carew, Pettigrove, & Hoffmann, ; Cranston et al, ; Ekrem, Stur, & Hebert, ; Ekrem, Willassen, & Stur, ; Montagna, Mereghetti, Lencioni, & Rossaro, ; Pfenninger, Nowak, Kley, Steinke, & Streit, ; Sinclair & Gresens, ; Stur & Ekrem, ), Culicidae (Ashfaq et al, ; Cywinska, Hunter, & Hebert, ; Kumar, Rajavel, Natarajan, & Jambulingam, ; Versteirt et al, ; Wang et al, ), Hybotidae (Nagy, Sonet, Mortelmans, Vandewynkel, & Grootaert, ), Muscidae (Renaud, Savage, & Adamowicz, ), Psychodidae (Gutiérrez, Vivero, Vélez, Porter, & Uribe, ; Krüger, Strüven, Post, & Faulde, ; Kumar, Srinivasan, & Jambulingam, ; Nzelu et al, ), Sciaridae (Eiseman, Heller, & Rulik, ; Heller, Köhler, Menzel, Olsen, & Gammelo, ; Heller & Rulik, ; Latibari, Moravvej, Heller, Rulik, &...…”
Section: Introductionmentioning
confidence: 99%